Pengaruh Media Tanam terhadap Pertumbuhan Bibit Pisang Cavendish (Musa cavendishii Lamb.) Asal Kultur Jaringan - TENTI, PAULA TIBURSIANA LOLI; WIJANA, GEDE; PRADNYAWATHI, NI LUH MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2022)
Effect of Planting Media on Growth of Cavendish Banana Seedlings ( Musa Cavendishii  Lamb.) from Tissue Culture Good quality planting media is needed in plant cultivation. By obtaining the right planting media can support and increase the growth and yield of plants. This study aims to determine the effect of planting media on the growth of Cavendish banana seedlings from tissue culture and to find the best growing media for Cavendish banana seedlings from tissue culture. The research was carried out from December 2019-March 2020 at the Experimental Garden of the Faculty of Agriculture, Udayana University, Jalan Pulau Moyo, Pedungan, South Denpasar District, Denpasar City. The study used a single factor randomized block design consisting of 4 treatments, namely soil, soil + rice husk, soil + husk charcoal and soil + rice husk + husk charcoal. The results showed that the planting medium had a very significant effect on the number of leaves variable, had a significant effect on root length and had no significant effect on seedling height, stem diameter, leaf chlorophyll, leaf area, number of roots, root fresh weight, crown fresh weight and total fresh weight. seeds. The best planting media mix for the growth of banana seedlings was a mixture of soil + rice husk + husk charcoal planting media with a higher value than soil planting media as control, soil + rice husk and soil + husk charcoal.